Effective Removal of Phosphate from Waste Water Based on Silica Nanoparticles - Tan Tai Nguyen (Journal of Chemistry)
This study explored the potential application of silica nanoparticles (SiNPs) prepared from rice husk ash (RHA) to reuse phosphate from aqueous solution. The physicochemical analysis illustrated that the SiNPs, which were extracted from waste biomass, have a nonuniform shape with a size range of a few nanometer to hundreds of nanometers, a surface area of 15.56 m2·g−1, and an adsorption pore width of 4.06 nm. Those results carried out the possibility to utilize the SiNPs for removal of phosphate. Findings from the batch sorption experiments showed that the phosphate adsorption was controlled by experimental parameters, i.e., pH, adsorbent dosage, concentration of adsorbate, and adsorption time. The experimental results showed that the maximum phosphate adsorption capacity of SiNPs was achieved at around 9.08 mg·g−1 at adsorption conditions, i.e., pH 7, SiNPs dosage of 0.3 g, and adsorption time of 90 min. The phosphate removal based on SiNPs will offer several benefit such as an effective and low cost method, reliable to reuse as an effective slow release phosphate fertilizer.